REDUPLIKASI ADVERBIA SEBAGAI PROSEDE MORFOLOGIS PALING DOMINAN DALAM BAHASA INDONESIA: PERSPEKTIF PRAGMATIK SISTEMIK - R. Kunjana Rahardi (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: Research on the reduplication of open and closed word classes in Indonesian language morphology in a systemic pragmatic perspective was carried out in order to respond to this reality. The research problem is formulated as follows, (1) What are the manifestations of open word class reduplication in Indonesian morphological procedures from a systemic pragmatic perspective; (b) What is the most dominant class of word reduplication in Indonesian morphological procedures? The data of this study were collected by listening and competent methods. The listening method used is applied by note taking and recording techniques. As for the proficient methods used, the proficiency techniques are proficient and the techniques of proficiency are not upfront. The proficient methods and techniques are supplemented by note taking and recording techniques. The data that has been presented well, has been classified and properly typified, then analyzed using the distribution analysis method and the method of matching analysis. The conclusions of this study are: (1) Reduplication of adverb word classes occurs with a very dominant use of informal Indonesian in electronic mass media such as those contained in television. (2) Reduplication both in the word classes of adverbs, verbs, adjectives, nouns, and numerals found in this study partly changes the word class and meaning, changes the word class but does not change the meaning. (3) The systemic pragmatic perspective can be used to interpret the reduplication more precisely because in this perspective the internal aspects of the language as well as the external aspects of the language are equally considered.Abstrak: Penelitian reduplikasi kelas kata terbuka dan tertutup dalam prosede morfologi bahasa Indonesia dalam perspektif pragmatik sistemik ini dilakukan dalam rangka merespons kenyataan ini. Masalah penelitian ini dirumuskan sebagai berikut, (1) Apa sajakah manifestasi reduplikasi kelas kata terbuka dalam prosede morfologis bahasa Indonesia ditinjau dari perspektif pragmatik sistemik; (b) Reduplikasi kelas kata apakah yang paling dominan terjadi dalam prosede morfologis bahasa Indonesia? Data penelitian ini dikumpulkan dengan metode simak dan metode cakap. Metode simak yang digunakan diterapkan dengan teknik catat dan teknik rekam. Adapun metode cakap yang digunakan adalah teknik cakap semuka dan teknik cakap yang tidak semuka. Metode dan teknik cakap itu dilengkapi dengan teknik catat dan teknik rekam. Data yang telah tersaji dengan baik, telah diklasifikasi dan ditipifikasi dengan baik, selanjutnya dianalisis dengan menggunakan metode analisis distribusional dan metode analisis padan. Simpulan penelitian ini adalah, (1) Reduplikasi kelas kata adverbia terjadi dengan sangat dominan dalam pemakaian bahasa Indonesia informal di media massa elektronik seperti yang terdapat dalam televisi. (2) Reduplikasi baik dalam kelas kata adverbia, verba, adjektiva, nomina, maupun numeralia yang ditemukan dalam penelitian ini sebagian mengubah kelas kata dan makna, mengubah kelas kata tetapi tidak mengubah makna. (3) Perspektif pragmatik sistemik dapat digunakan untuk memaknai reduplikasi tersebut secara lebih tepat karena dalam perspektif ini aspek internal kebahasaan maupun aspek eksternal kebahasaan sama-sama dipertimbangkan.